Prescription opioid abuse: pharmacists’ perspective and response - Cochran G; Hruschak V; DeFosse B; Hohmeier KC (Dove Medical Press, 2016)
Gerald Cochran,1,2 Valerie Hruschak,2 Brooke DeFosse,3 Kenneth C Hohmeier3 1Department of Psychiatry, School of Medicine, 2School of Social Work, University of Pittsburgh, Pittsburgh, PA, 3Department of Clinical Pharmacy, College of Pharmacy, University of Tennessee, Memphis, TN, USA Abstract: Opioid medication abuse and overdose are major concerns for public health, and a number of responses to address these issues have taken place across the US. Pharmacists and the pharmacy profession have made important contributions as a part of the response to this national crisis. This article provides a brief review of the antecedents, driving forces, and health status of patients involved in the opioid medication and overdose epidemic. This review further discusses pharmacy-based actions that have been undertaken to address this issue, including prescription drug monitoring, take-back, and naloxone training/distribution programs. This review likewise examines current efforts underway in the field to educate practitioners and needed future steps that must be taken by pharmacists in order to continue the profession’s pivotal role in working toward resolving this national public health problem. In particular, evidence and arguments are presented for proactively identifying and intervening with patients who abuse and/or are at risk for overdose. Continued and active engagement by pharmacists in these efforts has the potential to result in important reductions in opioid medication abuse and overdose and improvements for patient’s health. Keywords: opioid pain medication, addiction, pharmacy practice